1997
DOI: 10.1097/00000478-199709000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Graft-Versus-Host Disease: A Blinded Histologic Study

Abstract: Acute graft-versus-host disease (GvHD) of the upper gastrointestinal (GI) tract is common after allogeneic bone marrow transplantation (BMT). However, diagnosis cannot be made on clinical presentation and endoscopic findings alone, because these are nonspecific, and histologic confirmation is often desirable. The diagnosis of gastric GvHD is often based on subtle findings with considerable potential for variability in interpretation. Evaluation of the reproducibility of diagnosis and recognition of histologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 17 publications
0
61
1
Order By: Relevance
“…The latter may reflect the absence of consensus for the definition of histological signs of acute GI-GVHD, with the minimum criterion being the presence of apoptotic lesions, although not specific of GI-GVHD. 16,22 Also, several studies have reported discrepancies between the clinical and histological localizations of acute GI-GVHD, 23,24 which is represented in our study by the case of one patient who had clinical symptoms of grade 2 acute GI-GVHD, but had a morphologically normal sigmoidoscopy and only grade 1 histological acute GI-GVHD. Therefore, the segment of the gastrointestinal tract that should be biopsied for diagnosis of acute GI-GVHD remains subject to controversy.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The latter may reflect the absence of consensus for the definition of histological signs of acute GI-GVHD, with the minimum criterion being the presence of apoptotic lesions, although not specific of GI-GVHD. 16,22 Also, several studies have reported discrepancies between the clinical and histological localizations of acute GI-GVHD, 23,24 which is represented in our study by the case of one patient who had clinical symptoms of grade 2 acute GI-GVHD, but had a morphologically normal sigmoidoscopy and only grade 1 histological acute GI-GVHD. Therefore, the segment of the gastrointestinal tract that should be biopsied for diagnosis of acute GI-GVHD remains subject to controversy.…”
Section: Discussionmentioning
confidence: 64%
“…New PET tracers targeting specific targets are under clinical investigation in other settings and might be used more specifically than 18 F-FDG in GI-GVHD. Washington et al 16 demonstrated that the crypt cell apoptosis was one of the histological hallmark of GI-GVHD. Thus, apoptotic cells might be considered as a good target to improve Sp of PET imaging in GI-GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported GVHD-like histopathologic findings in immunodeficiency states including HIV infection, common variable immunodeficiency, and severe T cell deficiency, and also following renal transplantation. 7,[21][22][23] Hematopoietic stem cell transplantation can lead to immunodeficiency states due to myeloablative conditioning regimens or use of immunosuppressants. It is possible that GVHD-like histologic changes are related to immunodeficiency in some of our asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] It has been suggested that clinical features of GVHD differ by geographic area or among races because of different immunogenetic backgrounds. [11][12][13][14] Therefore, the clinical significance of upper GI GVHD in previous reports may not necessarily apply to patients outside the United States.…”
mentioning
confidence: 99%
“…More recently, the stomach has been shown to be an important area for the histological diagnosis of gastrointestinal GVHD even when diarrhoea is the main symptom and the small bowel is more damaged. 91,92 Chronic GVHD rarely involves the stomach.…”
Section: Cytomegalovirus Gastritismentioning
confidence: 99%